(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
This article analyzes the manifestation of traditional attitudes to life in the socio-home melodiousness migrant workers themes and their transformation under the influence of socio-economic factors. Particular attention is given to changes in the components of the national rice Ukrainian mentality depending on the social and historical conditions.